Moloch's Gauntlet: New Undergraduate Pedagogical Perspectives in Minecraft - Calcagnile, Angelica; Torre, Nat; Rochon, Andrew; Fox, Theodore (Loading, 2025)
As undergraduate students turned research assistants, building Moloch’s Gauntlet, an in-game escape room, became a lived experiment in modded Minecraft as a pedagogical tool. Our project explores three ideas: 1) how dismantling the game’s representational aesthetics links it to the wider body of knowledge that functions as an alternate academic space, 2) how selectively concealing and revealing the game’s mechanisms leads to procedural elaboration, inviting participation in the creative process, and 3) that modded Minecraft functions as an open platform that makes the iterative game design process accessible, teaching design through play without the barrier of complex computer science foundations. Our own experience, first as students and then as undergraduate student-researchers, suggests that engaging students with techniques that move beyond familiar call-and-response, problem-and-solution approaches, can result in a transformative outcome for students and educators alike.